Perirhinal Cortex LTP Does Not Require Astrocyte BDNF-TrkB Signaling - Beatrice Vignoli; Marco Canossa (Cells, 2022)
Neurons release and respond to brain-derived neurotrophic factor (BDNF) with bursts of brain activity. BDNF action is known to extend to peri-synaptic astrocytes, contributing to synaptic strengthening. This implies that astrocytes have a set of dynamic responses, some of which might be secondary to activation of the tropomyosin tyrosine kinase B (TrkB) receptor. Here, we assessed the contribution of BDNF to long-term synaptic potentiation (LTP), by specifically deleting TrkB in cortical astrocytes. TrkB deletion had no effect on LTP induction, stabilization and maintenance, indicating that TrkB signaling in astrocytes is extraneous to transducing BDNF activity for synaptic strengthening.